TANTANGAN DAN PELUANG BISNIS KONTRAK MANAJEMEN HOTEL DI ERA ADAPTASI KEBIASAAN BARU PADA PURI SIGNATURES DI BALI, INDONESIA - Ni Wayan Sumariadhi; I Wayan Wijayasa; Luh Kadek Budi Martini; I Wayan Sonder (Journal of Applied Management Studies, 2023)
This article is the result of a case study research regarding the impact of the Covid-19 pandemic on the Hotel Management Contract business (hotel operator business) at Puri Signatures located in Bali, Indonesia. Research finds that the Covid-19 pandemic has affected companies from management to operational levels. At the management level, the Covid-19 pandemic has affected the ownership structure, organizational structure, and the change of brand from Puri Villas Indonesia to Puri Signatures. At the operational level, there have been major changes in terms of the cooperative relationship between management and clients, employment, marketing, partnership, and finance. However, the Covid-19 pandemic has provided an opportunity for companies to explore the performance of companies that are experiencing downsizing through new partnerships with a profit sharing system, and improve strategies towards digital marketing.